Identification of Potential Medicinal Plants in Tawang Selubang Forest in Kelam Permai Subdistrict, Sintang Regency, West Kalimantan - Fathul Yusro; Yeni Mariani; Erianto; Gusti Hardiansyah; Hendarto; Aripin; Deni Nurdwiansyah (Biotropic : The Journal of Tropical Biology, 2020)
The Tawang Selubang Forest, located in the Other Use Area (APL) is determined by the regional government of Sintang Regency, West Kalimantan as the Hutan Tutupan (forest cover). This forest has great benefits for the community, one of which is as a source of medicinal plants. This research aims to identify the potential species of medicinal plants in the Tawang Selubang Forest Cover. Inventory of potential medicinal plants is done by making a square (0.5 Ha) cluster design (100 mx 100 m) in which there are 5 circular plots. Each plot contained several circular subplots that functioned for observation of seedling level (r= 1 m), stake (r= 2 m), pole (r= 5 m) and tree (r= 17.8 m). The number of plant species found in the Tawang Selawang Forest Cover were 47 species and 27 species were medicinal plants. Some species of medicinal plants that have a high density and important value index are Xanthophyllum amoenum Chadat, Antidesma montanum Blume, Nephelium maingayi Hiern, Palaquium gutta (Hook.) Baill and Syzygium lineatum (DC.) Merr. & J.Parn .